Answer:
a = 2x
b = 3
Explanation:
Consider the sum of cubes identity
a³ + b³ =(a + b)(a² -ab +b²)
for the polynomial 8x³ +27, we factorise
8x³ + 27
∛8 = 2
∛8 = x
∛27 = 3
Therefore, we can say that :
8x³ + 27 = (2x)³ + 3³
Using this: a³ + b³ =(a + b)(a² -ab +b²)
We can say that
a = 2x
b = 3
To confirm that: a = 2x and b = 3 we factorise 8x³ + 27
= (2x)³ + 3³
= (2x + 3)((2x)²− 2x × 3 + 3²)
= (2x + 3)(4x² - 6x + 9)
= 8x³ - 12x² +18x + 12x² - 18x + 27
= 8x³ + 27
Therefore, a = 2x and b = 3 is correct.
=